Influence of Anthropogenic Sounds on Insect, Anuran and Bird Acoustic Signals: A Meta-Analysis - Gomes, Lidiane; Solé, Mirco; Sousa-Lima, Renata S.; Baumgarten, Júlio Ernesto (Frontiers in Ecology and Evolution, 2022)
Acoustic communication is a way of information exchange between individuals, and it is used by several animal species. Therefore, the detection, recognition and correct understanding of acoustic signals are key factors in effective communication. The priority of acoustic communication is effectiveness rather than perfection, being effective avoids affecting the sound-based communication system of the species. One of the factors that can affect effective communication is the overlap in time and frequency during signal transmission, known as signal masking. One type of sound that can cause masking is anthropogenic noise, which is currently increasing due to urban growth and consequently motorized transportation and machinery. When exposed to anthropogenic noise, animals can use compensatory mechanisms to deal with sound masking, such as the modification of acoustic parameters of their acoustic signal. Here, we performed a meta-analysis investigating whether different taxa have a general tendency for changes in acoustic parameters due to anthropogenic noise, we used taxa and acoustic parameters available in the literature that met the minimum criteria to perform a meta-analysis. We hypothesized that animals exposed to anthropogenic noise use compensation mechanisms, such as changes in dominant, maximum or minimum frequencies, call duration, note duration and call rate to deal with masking. We performed a meta-analysis, which synthesized information from 73 studies comprising 82 species of three taxa: insects, anurans and birds. Our results showed that in the presence of anthropogenic noise, insects did not change the acoustic parameters, while anurans increased call amplitude and birds increased dominant frequency, minimum and maximum frequencies, note duration and amplitude of their songs. The different responses of the groups to anthropogenic noise may be related to their particularities in the production and reception of sound or to the differences in the acoustic parameters considered between the taxa and also the lack of studies in some taxa.